Serum Lipocalin-2 Levels Are Increased and Independently Associated With Early-Stage Renal Damage and Carotid Atherosclerotic Plaque in Patients With T2DM - Gan, Jing; Zheng, Yu; Yu, Qiongli; Zhang, Yingchao; Xie, Wei; Shi, Yaru; Yu, Ning; Yan, Yu; Lin, Zhuofeng; Yang, Hong (Frontiers in Endocrinology, 2022)
Objectives: Diabetic nephropathy (DN), one of the major complications of diabetes mellitus, is the major causes of end-stage renal failure that finally increase the risk of cardiovascular disease and mortality. The aim of this study is to explore the relationship between serum lipocalin-2 (LCN-2) levels and DN, carotid atherosclerotic plaque (CAP) in patients with type 2 diabetes mellitus (T2DM). Methods: We have performed a prospective study of 749 T2DM patients with or without DN. Blood samples were collected and used to test serum LCN-2 levels, renal function, as well as biochemical parameters. CAP in these subjects was determined by ultrosongraphy. Results: In these 749 subjects with T2DM, an increased morbidity of CAP was observed in T2DM patients with DN as compared with those without this complication (P < 0.05). Interestingly, serum LCN-2 levels were signficantly increased in T2DM patients with DN or CAP compared with T2DM alone [97.71 (71.49-130.13) vs. 77.29 (58.83-115.05) ng/ml, P < 0.001]. In addition, serum LCN-2 levels in T2DM patients with DN and CAP were significantly higher than that of T2DM patients with DN or CAP [131.37 (101.43-182.04) vs. 97.71(71.49-130.13) ng/ml, P < 0.001]. Furthermore, serum LCN-2 levels were positively correlated with haemoglobin A1c, systolic blood pressure, hypertension, CAP and DN, as well as renal function factors including uric acid, creatinine , estimated glomerular filtration rate and urinary albumin-to-creatinine ratio respectively (P < 0.05), but negatively correlated with HDL-c (P < 0.05). The multinomial logistic regression analysis showed that serum LCN-2 was independently associated with DN and CAP in patients with T2DM after adjustment for risk factors (P < 0.001). Conclusions: Early-stage renal damage is a risk factor associated with the incidence of CAP in patients with T2DM. Serum LCN-2 is significantly increased and associated with early-stage renal damage and the incidence of CAP in patients with T2DM.